2015
DOI: 10.4103/2277-9175.170242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of capillary and venous blood glucose levels using glucometer and laboratory blood glucose level in poisoned patients being in coma

Abstract: Background:Poisoning is one of the most common medical presentations in a hospital. Hypoglycemic patients are at increased risk of toxicity. The purpose of this study was to compare capillary blood glucose and venous blood glucose measurements using glucometer against laboratory blood glucose in case of poisoned patients being in coma.Materials and Methods:During the 6-month study period, a random sample of 98 patients was admitted in the Department of Poisoning Emergency and Clinical Toxicology of Noor Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Nevertheless, previous studies conclude that there exists a strong correlation between capillary and intravenous blood glucose samples ranging from r=0.933 to 0.973 ( P <0.01). Moreover, no significant time lag during glucose excursions was observed among the ISF, and capillary and venous glucose levels (38, 39). In addition, if capillary glucose measures are less robust than venous blood glucose measures and do indeed introduce greater variance in our data, this increased noise would have biased our finding towards the null hypothesis.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, previous studies conclude that there exists a strong correlation between capillary and intravenous blood glucose samples ranging from r=0.933 to 0.973 ( P <0.01). Moreover, no significant time lag during glucose excursions was observed among the ISF, and capillary and venous glucose levels (38, 39). In addition, if capillary glucose measures are less robust than venous blood glucose measures and do indeed introduce greater variance in our data, this increased noise would have biased our finding towards the null hypothesis.…”
Section: Discussionmentioning
confidence: 88%
“…It was determined that though it was appropriate to use fasting CG levels to determine the prevalence of diabetes in populations, it should not be used to reliably diagnose diabetes in individuals (Tirimacco et al, 2010). In addition, the venous blood glucose value was reported to give better results than the capillary blood glucose value in the coma patients (Yaraghi et al, 2015). In a study with intensive care patients, Lonjaret et al (2012) compared capillary and arterial blood glucose measurements with central laboratory arterial glucose measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Funk DL et al (11), relative and absolute contraindications of measured capillary were used to measure the blood glucose of poisoned patients in coma due to environmental vasoconstriction reasons, cold extremities, low blood pressure, inflammation and local edema; results of this study were consistent with those of the current study conducted based on peripheral vascular and finger artery damages, coldness, and local inflammation of damaged fingers and obvious difference between sugar levels of two fingers, especially the crushed fingers that later were gangrenous and amputated. In a study by Yaraghi et al (12) performed in Isfahan on poisoned patients who were in coma, a comparison of capillary and venous blood samples and also glucose levels measured by the glucometer and laboratory tests showed that venous blood glucose samples measured by the glucometer were acceptable, but capillary blood glucose samples measured by the glucometer from patients in coma were not suggested. In other words, the problem was not due to using the glucometer, but due to changes in capillaries, due to local and inflammatory factors and vascular changes, which was also confirmed by the current study.…”
Section: Discussionmentioning
confidence: 99%